Ethnomedicinal Importance of Invasive Alien Flora of Latehar and Hazaribagh Districts: Jharkhand - Divakara, B. N.; Prasad, Santosh (Indian Forester, 2015)
During the process of investigation and documentation on invasive alien flora available in Latehar and Hazaribagh districts, some of the interesting facts on potential medicinal uses were closely noted based on experimented and proven evidences by interrogation with the ethnic people especially tribes like Munda and Birhore. In this paper the most commonly used invasive alien medicinal species viz. Ageratum conyzoides, Argemone mexicana, Calotropis procera, Cassia alata, Cassia tora, Cuscuta reflexa, Datura metel, Eclipta prostrata, Emilia sonchifolia, Eupatorium odoratum, Hyptis suaveolens, Leonotis nepataefolia, Opuntia stricta, Scoparia dulcis, Sida acuta, Solanum torvum, and Tridax procumbens possessing different medicinal properties like expectorant, styptic and antibiotic, antifungal, antispasmodic, anodyne, febrifuge, refrigerant and enteritis are discussed.